2016
DOI: 10.1098/rspb.2016.0246
|View full text |Cite
|
Sign up to set email alerts
|

Chronic neonicotinoid pesticide exposure and parasite stress differentially affects learning in honeybees and bumblebees

Abstract: Learning and memory are crucial functions which enable insect pollinators to efficiently locate and extract floral rewards. Exposure to pesticides or infection by parasites may cause subtle but ecologically important changes in cognitive functions of pollinators. The potential interactive effects of these stressors on learning and memory have not yet been explored. Furthermore, sensitivity to stressors may differ between species, but few studies have compared responses in different species. Here, we show that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
76
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 77 publications
(82 citation statements)
references
References 56 publications
5
76
0
1
Order By: Relevance
“…One of the substances most commonly used in crop protection and registered in over 120 countries is imidacloprid (IMD) (Jeschke, Nauen, Schindler, & Elbert, 2011). It is known that IMD, is an agonist of the nicotinic acetylcholine receptor (nAChRs) on the postsynaptic membrane, and like other compounds from this group of pesticides, it affects the central nervous system (CNS) of insects (Brown, Ihara, Buckingham, Matsuda, & Sattelle, 2006;Matsuda, Shimomura, Ihara, Akamatsu, & Sattelle, 2005) and subsequently the insect's physiology and behavior (Desneux, Decourtye, & Delpuech, 2007;Piiroinen & Goulson, 2016;Teeters, Johnson, Ellis, & Mario, 2012;Van Dijk, Van Staalduinen, & Van der Sluijs, 2013). For example, it has been shown that sublethal doses of IMD have an adverse effect on the bee's sense of smell and memory (Decourtye, Devillers et al, 2004, Decourtye, Armengaud et al, 2004Kirchner, 1999;Williamson, Baker, & Wright, 2013), as well as on the insects' intensity of feeding (Schneider, Tautz, Gruenewald, & Fuchs, 2012;Yang, Chuang, Chen, & Chang, 2008), territorial disorientation (Hatjina, Papachristoforou, Charistos, Bouga, & Arnold, 2012;Henry et al, 2012), and neurophysiologic changes (Goulson, 2013;Guez, Suchail, Gauthier, Maleszka, & Belzunces, 2001a, 2001bLambin, Armengaud, Raymond, & Gauthier, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…One of the substances most commonly used in crop protection and registered in over 120 countries is imidacloprid (IMD) (Jeschke, Nauen, Schindler, & Elbert, 2011). It is known that IMD, is an agonist of the nicotinic acetylcholine receptor (nAChRs) on the postsynaptic membrane, and like other compounds from this group of pesticides, it affects the central nervous system (CNS) of insects (Brown, Ihara, Buckingham, Matsuda, & Sattelle, 2006;Matsuda, Shimomura, Ihara, Akamatsu, & Sattelle, 2005) and subsequently the insect's physiology and behavior (Desneux, Decourtye, & Delpuech, 2007;Piiroinen & Goulson, 2016;Teeters, Johnson, Ellis, & Mario, 2012;Van Dijk, Van Staalduinen, & Van der Sluijs, 2013). For example, it has been shown that sublethal doses of IMD have an adverse effect on the bee's sense of smell and memory (Decourtye, Devillers et al, 2004, Decourtye, Armengaud et al, 2004Kirchner, 1999;Williamson, Baker, & Wright, 2013), as well as on the insects' intensity of feeding (Schneider, Tautz, Gruenewald, & Fuchs, 2012;Yang, Chuang, Chen, & Chang, 2008), territorial disorientation (Hatjina, Papachristoforou, Charistos, Bouga, & Arnold, 2012;Henry et al, 2012), and neurophysiologic changes (Goulson, 2013;Guez, Suchail, Gauthier, Maleszka, & Belzunces, 2001a, 2001bLambin, Armengaud, Raymond, & Gauthier, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…The results demonstrated here in bumblebees are congruent with the outcomes of prior studies investigating interactions between neonicotinoid exposure and immunity in honeybees (Alaux et al., ; Di Prisco et al., ; Brandt et al., ; López et al., ). This is not a trivial extension, as honeybees and bumblebees, while both highly susceptible, have been suggested to differ in their detoxification of neonicotinoids (Cresswell, Robert, Florance, & Smirnoff, ), and neonicotinoid exposure and parasite stress has been shown to have differential effects in the two groups of bees (Piiroinen & Goulson, ). The reduction in antimicrobial activity in B. impatiens is in contrast to a recent study showing elevated AMP expression following imidacloprid exposure (Simmons & Angelli, ).…”
Section: Discussionmentioning
confidence: 99%
“…Numerous global factors are thought to contribute to this alarming phenomenon, including habitat loss and fragmentation, suboptimal diet, diseases and the detrimental effects of sublethal, chronic pesticide exposure (Goulson, Nicholls, Botías, & Rotheray, ; Vanbergen et al, ). Besides affecting pollinator navigation abilities (Fischer et al., ; Henry et al., ; Jin, Klein, Leimig, Bischoff, & Menzel, ; Stanley, Russell, Morrison, Rogers, & Raine, ), cognitive abilities (Decourtye, Devillers, Cluzeau, Charreton, & Pham‐Delègue, ; Farooqui, ; Gauthier, ; Kessler et al., ; Piiroinen & Goulson, ; Stanley, Smith, & Raine, ; Williamson, Baker, & Wright, ; Williamson, Moffat, et al., ) and reproduction (Baron, Raine, & Brown, ; Sandrock et al., ; Whitehorn, O'Connor, Wackers, & Goulson, ), the immune suppressive effect of sublethal pesticide doses and the resulting elevated susceptibility of pollinators to pathogens (Baron et al., ; Brandt, Gorenflo, Siede, Meixner, & Büchler, ; Di Prisco et al., ; Doublet, Labarussias, de Miranda, Moritz, & Paxton, ; Fauser‐Misslin, Sadd, Neumann, & Sandrock, ; Hernández López et al., ; previous studies summarized in James & Xu, ) are of particular concern (Sánchez‐Bayo et al., ).…”
Section: Of Pollinators Pesticides and Parasitesmentioning
confidence: 99%
“…Assessing the impact of pesticides on pollinator health by sublethal chronic exposure requires a holistic view of the problem. In recent years, research has started to uncover the side‐effects of sublethal neonicotinoid exposure on cognitive abilities, including pollinator navigation and learning (Decourtye et al., ; Farooqui, ; Fischer et al., ; Gauthier, ; Goulson et al., ; Henry et al., ; Jin et al., ; Kessler et al., ; Piiroinen & Goulson, ; Stanley et al., , ; Williamson, Baker, et al., ; Williamson, Moffat, et al., ). A similar intensity of research effort now needs to be focused on the sublethal effects of neurotoxic pesticides on insect immunity.…”
Section: Future Directionsmentioning
confidence: 99%